Psychological flexibility and self-critical rumination: A serial mediation between adverse childhood experiences and mental well-being in adulthood - Birni, Gaye; Erus, Seher Merve; Satici, Seydi Ahmet; Deniz, M. Engin (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Adverse childhood experiences (ACEs) may affect individuals' neurological and cognitive development and may cause some mental health challenges later in adulthood. Previous research show emotionally abused children may internalize self-critical tendencies, leading to an increased display of self-critical rumination. And one way to cope with self-criticism might be through psychological flexibility. This cross-sectional study investigated the serial mediation of psychological flexibility and self-critical rumination in the ACES-adult mental well-being link in a sample of 450 Turkish adults with the average age of 30.5. The results showed that psychological flexibility and self-critical rumination fully mediated the path from ACEs to mental well-being. The goodness of the fit indexes indicated a good fit. ACEs were associated with an increased tendency towards self-critical rumination, potentially perpetuating a cycle where individuals who were subjected to abuse in childhood may internalize and replicate harmful behaviors in adulthood. However, through psychological flexibility, adults with ACEs possess the capacity to confront and acknowledge these traumatic events and their effects. By embracing psychological flexibility, individuals may tap into their mental resources, facilitating a pathway towards healing and wellbeing. Thus, fostering psychological flexibility might be a significant factor in promoting mental well-being among adults with a history of ACEs.
Keywords: Adverse childhood experiences; Mental well-being; Psychological flexibility; Self-critical rumination; Self-criticism; ACTION QUESTIONNAIRE-II; COMMITMENT THERAPY; VALIDITY ANALYSIS; TURKISH VERSION; INFLEXIBILITY; ACCEPTANCE; RELIABILITY; COMPASSION; Psychology